PENGARUH PENGETAHUAN KEWIRAUSAHAAN, PENGGUNAAN E-COMMERCE DAN TEMAN SEBAYA TERHADAP INTENSI BERWIRAUSAHA PADA MAHASISWA PENDIDIKAN EKONOMI - Elisa Yena Serni; Fernando Saragih (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
Low entrepreneurial intentions are one of the crucial problems that can affect economic conditions. Based on this, researchers are interested in analyzing this problem and looking at the various factors that influence it in terms of the Theory of planned behavior. In this study, researchers focused on the factors of entrepreneurial knowledge, use of e-commerce, and peers. This quantitative approach with the ex post facto method where the analysis uses multiple linear regression with the application of SPSS version 21. This study uses 53 questionnaires (consisting of 14 from X1, 15 from X2, 13 from X3, and 11 from Y) with a sample of 209. Based on data analysis (both multiple linear regression and hypothesis testing) the results show that entrepreneurial knowledge and use of e-commerce have a positive and significant effect, where these two variables will encourage entrepreneurial development and facilitate the entrepreneurial process while peers show negative and negative effects. sig. This influence is formed because the peer environment is not mature enough in responding to various conditions and situations around them.